Applying Cognitive Semantics to Infer Psychological Teachings From The Quran/ توظيف علم الدلالة المعرفية لاستنباط التعاليم النفسية من القرآن - Esfahani, Ali Banaeian; Rizi, Elahe Sadat Mirsafaei (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study applies theories of cognitive semantics to uncover psychological insights from the Quran. It focuses on conceptual metaphor theory, mental schemas, mental spaces, and embodied cognition. The research aims to understand the relationship between language and cognition in religious texts, emphasizing psychological aspects related to emotional regulation, achieving spiritual balance, and enhancing psychological resilience. A descriptive analytical approach is employed to apply these theories to Quranic texts. For example, metaphors such as